Respuesta :

Answer:

see explanation

Step-by-step explanation:

(a)

The sum of the 3 angles in a triangle = 180°

Subtract the sum of the given angles from 180° for B

∠ B = 180° - (90 + 63)° = 180° - 153° = 27°

(b)

Using the sine ratio in the right triangle

sin63° = [tex]\frac{opposite}{hypotenuse}[/tex] = [tex]\frac{BC}{AB}[/tex] = [tex]\frac{15}{x}[/tex] ( multiply both sides by x )

x × sin63° = 15 ( divide both sides by sin63° )

x = [tex]\frac{15}{sin63}[/tex] ≈ 16.8 ( to 1 dec. place )

(c)

Using the tangent ratio in the right triangle

tan63° = [tex]\frac{opposite}{adjacent}[/tex] = [tex]\frac{BC}{AC}[/tex] = [tex]\frac{15}{y}[/tex] ( multiply both sides by y )

y × tan63° = 15 ( divide both sides by tan63° )

y = [tex]\frac{15}{tan63}[/tex] ≈ 7.6 ( to 1 dec. place )